Adopting Bioinformatics and Neural Network Deductions to Extrapolate the Structure and Evolutionary Dynamics of Helix Partnerships (Global Journal of Management and Business Research, 2018)
Helices are twisting writhing complex structures in space and synonymous to organizational growth innovation partnerships and direction of partnership evolution Etzkowitz revolutionary paper set the pace for the application of varying principles of science to the analysis of organizational networks Especially so for studies involving industry university and government as they both seek to generate innovation create wealth and achieve optimal levels of control We adopt principles from the fields of bioinformatics to showcase the internal dynamics and structure of organizational networks
Keywords: innovation; network; triple helix; dna; neural networks; university